Effect of indomethacin suppository on the prevention of pancreatitis after endoscopic retrograde cholangiopancreatography: a Meta-analysis - PU Xinlin; JIANG Zhaoyou (Yixue xinzhi zazhi)
Objective To systematically evaluate the efficacy of indomethacin suppository on the prevention of post-endoscopic retrograde cholangiopancreatography (ERCP) pancreatitis (PEP).Methods CNKI, CBM, VIP, WanFang, PubMed, CENTRAL and Embase were searched to collect randomized controlled trials of indomethacin suppository for the prevention of acute PEP. The search period was from inception to April 20, 2024. Two authors screened the articles independently, extracted the target data and evaluated the risk of bias. Meta-analysis was conducted using software RevMan 5.3.Results A total of 20 studies with 4,238 patients were included. The results of Meta-analysis showed: the incidence of acute PEP [RR=0.47, 95%CI(0.35, 0.62)] and the incidence of hyperamylasemia [RR=0.55, 95%CI(0.44, 0.69)] in indomethacin group were significantly lower than the control group, the difference was statistically significant, but there was no statistically significant in acute severe PEP between indomethacin group and control group [RR=0.47, 95%CI(0.20, 1.11)]. In the indomethacin group, the amylase level at 6 h [MD=- 40.16, 95%CI(-48.93, -31.39)] after ERCP was significantly lower than the control group. There were no significant difference in the amylase level at 3 h [MD=-26.82, 95%CI(-162.46, 108.82)] and 24 h [MD=-83.75, 95%CI(-179.56, 12.05)] after ERCP between the indomethacin group and the control group.Conclusion Indomethacin suppository can decrease the incidence of acute PEP and hyperamylasemia after ERCP, and can reduce the amylase level at 6 h after ERCP.